Autism spectrum disorder and obstetric optimality: a twin study and meta‐analysis of sibling studies. (29th September 2021) - Gómez‐Vallejo, Sandra; Leoni, Marguerite; Ronald, Angelica; Colvert, Emma; Happé, Francesca; Bolton, Patrick
Abstract : Background: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder with a strong genetic basis. Recent studies have suggested that its aetiology is also influenced by environmental factors. Some of the most examined environmental factors are obstetric complications. However, the results are inconsistent. Methods: We aimed to explore the association between obstetric complications and autism in a population‐based twin sample using the Obstetric Enquiry Scale (OES), a scale that measures the presence or absence of pre‐, peri‐ and neonatal factors. Additionally, we report the meta‐analytic results for obstetrical factors reported in previously published sibling studies. Results: Our study included 115 cases pairs and 62 controls pairs and showed that children with autism and their unaffected co‐twins present significantly more obstetric complications than controls (ASD vs. controls β 1.26, CI 95% 1.11–1.40 p < .001; unaffected co‐twin vs. controls β 1.20, 95% CI 1.07–1.36 p < .003). However, we did not find statistically significant differences between children with ASD and their unaffected co‐twins (β .96, 95% CI 0.85–1.09, p 0.55). Meta‐analysis demonstrated that maternal hypertension (RR 1.35, CI 95% 1.23–1.48), uterine bleeding (RR 1.20 CI 95% 1.01–1.42) and exposure to antibiotic during pregnancy (1.11 CI 95% 1.00–1.22) increase risk of ASD. Conclusions: This study confirms that children with ASD and their unaffected twins show more obstetric complications than controls. However, these complications do not distinguish between ASD twins and their unaffected co‐twins. In addition, the meta‐analysis showed little influence of birth factors on ASD which suggests a shared familial liability for both obstetric complications and autism, rather than a causal association.